Analysis of reject pinhole hardfacing process for stellite alloy metal motorcycle engine valves - Aswin Domodite; Hilman Sholih; Irfan khoerudin (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
If businesses wish to compete in the industrial world, they must produce quality and process results. No matter how big or little, some goods will always fail to generate or be rejected in a production process. In this case, companies in the automobile sector have noticed an increase in the number of pinholes that have been returned during the past three months. The company established a maximum reject rate of 0.9% each month based on the rejected data; from May to July, the average reject rate was 0.23%. Finding the factors causing the surge in pinhole rejects that occurred between May and July is the aim of this investigation. The analysis showed that the increase in pinhole rejects was caused by a variety of variables, including machine, process, and human factors. Further examination disclosed alterations to the device's configuration and software, along with the operator's persistent incapacity to comprehend the process. As operations become less efficient, repair components build up in the manufacturing line area. As a result, an improvement plan is needed, which is put into action by giving operator training and rearranging the machine and its software according to process requirements. Operators with a greater understanding of the process yield better results and higher productivity. As a result, operator confidence will rise along with performance. It was discovered that after developments in the field of human resource development, the number of rejections had dropped. Before the repair was finished, the average reject from May to July 2023 was 0.23%; following the repair, the average reject from August to October 2023 was 0.09%